TINGGALAN BUNKER PERTAHANAN MILITER JEPANG SITUS LAPANGAN UDARA KENDARI II DI KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Ersa, Ersa Dwi Riyanto; Hasanuddin; Nur , Muhmmad; Muda, Khadijah Thahir (Universitas Hasanuddin, 2024)
The research aims to find out the shape of Japanese bunkers, the factors of bunker placement. the research uses survey methods, observation, supported by interviews and library data. the survey was carried out observing the surface of the land containing archaeological remains based on the results of the interpretation of old maps and aerial photographs obtained from library data. observation is carried out on the remains found, this stage includes description, documentation, and plotting. The analysis used morphological and contextual analysis. The results of the study, there are 56 bunkers which are divided into 5 forms of bunkers. Z, I, U, L, and b.5 forms of bunkers, classified into several parts in the form of Z 3. form I 4. Form U 3. L and B-shaped bunkers found 1 form. The placement of bunkers is influenced by environmental and safety factors.